Understanding the phase emergence of mesoporous silica - Yao, Lin (2015)
The cylinder-to-vesicle phase transition of mesoporous silica and the inter-dependence of the controlling factors are studied. (3-Mercaptopropyl)trimethoxylsilane (MPTMS) is used to alter the phase outcome of mesoporous silica from the cylindrical MCM-41 to the vesicular phase. Exploiting the phase selection at the critical time point of phase emergence allows investigation of the complex interactions among the ingredients. In this system, orderly cylindrical or vesicular phase directly emerges from the “clumps” of randomly mixed surfactant, co-surfactant, and silica precursor. The phase outcome depends on the exact ratio of the ingredients, provided that enough amounts of MPTMS can diffuse into the clumps before the hardening silica prevents the diffusion.